Bio-Inspired Hardware Using FPGAs - Ortega-Sanchez, Cesar (International Federation for Information Processing, 2005)
Bio-inspired electronic systems are inspired by processes and structures typically found in plants and animals. Such approach results in circuits with interesting properties that sometimes are very difficult to achieve by conventional design methodologies. This paper presents some ideas on why and how FPGAs and Bio-inspired systems make a good match. FPGAs can be the underlying "tissue" on which more complex structures and behaviours are developed. As an example, the Embryonics architecture is presented. Embryonic systems can be implemented using FPGAs as a sort of silicon substrate here Bio-inspired mechanisms that allow the circuits to "heal" take place.